Infrastructure and Facilities for the Development of On-Line Information Industry in India:A Proposal - Agrawal, I. K. (Journal of Information and Knowledge, 1992)
Presents a state-of-art infrastructural facility in telecommunication network in India. Presents a contemporary scenario on PSDN network and projects the future.